Marie Taglioni correspondence - Taglioni, Marie, 1804-1884.
ALS from Taglioni expressing regret that fatigue prevents her from keeping an appointment.
French ballerina.
Collection material in French.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Ballet dancers -- France; Dancers